DETERMINAN CASH HOLDINGS PADA 5 NEGARA DI ASIA TENGGARA - Weslie, Marcella; Imelda, Elsa (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this rese arch is to obtain empirical evidence ragrding the effects of economic risk toward cash holding. This research focuses on the industrial sector and consumer non-cyclist in 5 countries located in the Southeast Asia as subjects used, and are listed on the Stock Exchange in 2019-2021 conducted with a sample of 17 4 data. The data was collected by purposive sampling as the technique used in this research, and processed in EViews 12 program. It is shown that from this research, both economic risk and variance of interest rate significantly affects the cash holding positively. However, the cash holdings are affected negatively significant by variance of inflation risk.